EXTENDED MAST TERMINAL (EMT) LIGHTNING PROTECTION SYSTEM FOR HIGH VOLTAGE TRANSMISSION - Puja Pradinta, Wahyu
Indonesia is a tropical country with a high lightning density, more than 10 strikes/km2/year. The intensity of the lightning strike can cause potential disruption to the electricity transmission network. Based on electricity company (PLN) data, mostly blackouts happened caused by lightning strikes on transmission lines. Lightning strike on the transmission network is causing voltage elevation which generated by the peak lightning current (i), tower resistance (R), the steepness of the lightning current (di / dt) and the tower inductance (L). The increase of voltage elevation can cause insulator failure which can lead disruption such as backflashover and shieldingfailure. Its disruption can cause total blackout. To solve this problem, conventional protection systems are used, among others by improving the grounding of the tower legs, installing the Transmission Line Arrester (TLA), adding insulator pieces and increasing the number of ground wires. However, this protection system is not effective because it will only reduce the increase of voltage elevation due to peak currents and tower resistance. Whereas, voltage raise due to inductance and current steepness is still high. In order to reduce voltage elevation due to tower inductance, Extended Mast Terminal (EMT) as a lightning protection system innovation is proposed. EMT is a lightning protection system that prevents direct strikes in transmissions, its function is for safely capture and distribute lightning currents to the earth. This system consists of air terminals equipped with Early Streamer Emission (ESE) to ensure lightning current flows in the system and not through the tower structure. Down Conductor with low inductance which functions to reduce the voltage elevation affected by the inductance and current steepness. An integrated grounding system is used to spread lightning current to the ground. The control panel contains of a Lightning Event counter (LEC) and Magnetic Tape Measuring Instrument used as monitoring equipment.